Experimental research on the dynamic permeability of hydrate silty-clay reservoirs during water driven and exploitation - Lu, Jingsheng; Li, Dongliang; Liang, Deqing; Shi, Lingli; He, Yong; Xiong, Youming (Journal of Natural Gas Science and Engineering, 2021)
Natural gas hydrate (NGH) is one of the potential clean energy resources in the 21st century. The gas and water permeability of hydrate-bearing sediments (HBS) is a significant factor that can be used to evaluate the productivity of NGH. China's marine NGH mostly exists in silty-clay sediments which has a high risk of sand production. Thus, it is difficult to discuss the dynamic permeability of the HBS during exploitation with sand production. It restricts the sustainable and economical production of the HBS. This study put new insights into sand production experiments during depressurization production in hydrate silty-clay sediments. The results show that the NGH particle size (saturation) plays a role in retaining mud/sand during exploitation and it influences the abnormal permeability. From the relationship between particle size of gravel pack and permeability, a new relationship between the hydrate saturation (particle size) and permeability is proposed. The permeability of the HBS during exploitation presented increase-decrease-increase trends with a decrease in the NGH saturation.